A systematic literature review: which factors influence English and Welsh perceptions towards victims of child sexual abuse?. Issue 3 (1st September 2016) - Hatton, Victoria Anne; Duff, Simon
ABSTRACT: Negative perceptions towards child sexual abuse (CSA) victims are prevalent within society. This has potential implications for CSA victims in terms of its effects on victim well-being and legal proceedings. Although many studies have investigated which factors influence English and Welsh perceptions, a systematic review has not been conducted to synthesise findings. Nine electronic bibliographic databases, six grey literature databases and one gateway resource were searched. Hand-searches of journals and references were also conducted and field experts contacted. Following the application of the inclusion criteria, studies were quality assessed and data extracted. The search yielded 4182 studies of which 1501 duplicates and 2644 irrelevant studies were excluded. After a further 26 studies were excluded, 11 studies were included in the review. This revealed a sample of 3088 participants with 18 factors investigated. To acknowledge the heterogeneity of the data, a narrative data synthesis approach was used. The review identified firm conclusions regarding respondent gender, whereby males perceived CSA victims as more to blame, more culpable, less reliable and less credible. Other tentative conclusions are discussed. Potential implications of these findings are discussed in terms of professional services and the response victims receive during disclosure.